The Effectiveness of Supplementary Reading Materials in Improving Students’ Reading Comprehension: A Systematic Literature Review - Mustika; Ashadi; Joko Priyana (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2025)
This systematic literature review examined thirteen articles published between 2020 and 2024 in various countries, including Malaysia, China, Indonesia, the Philippines, and Cambodia, that addressed the broad issue of improving students' reading comprehension at various levels of education through supplementary reading materials. The purpose of this study was to assess the efficacy of these reading materials, determine the most beneficial types, and examine the variables influencing their success using the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. The results indicated that supplementary reading materials can improve students' post-test reading scores (mean score increased by 21.34%), motivation, engagement, vocabulary acquisition, language comprehension, and critical thinking skills. Older students responded better to text-based reading materials, while younger students benefited more from digital resources. A key factor influencing the impact of reading materials is their relevance to students' cultural and personal backgrounds. Future research is recommended to examine how supplementary teaching materials can be used in online and hybrid learning to improve learning outcomes in the digital age.